Factors affecting the genetic load in Drosophila: synergistic epistasis and correlations among fitness components. - Whitlock, M.C.; Bourguet, D. (Evolution, 2000)
Two factors that can affect genetic load, synergistic epistasis and sexual selection, were investigated in Drosophila melanogaster. A set of five chromosomal regions containing visible recessive mutations were put together in all combinations to create a full set of 32 homozygous lines fixed for different numbers of known mutations. Two measures of fitness were made for each line: productivity (a combined measure of fecundity and egg-to-adult survivorship) and competitive male mating success. Productivity, but not male mating success, showed a pattern of strong average synergistic epistasis, such that the log fitness declined nonlinearly with increasing numbers of mutations. Synergistic epistasis is known to reduce the mutation load. Both fitness components show some positive and some negative interactions between specific sets of mutations. Furthermore, alleles with deleterious effects on productivity tend to also diminish male mating success. Given that male mating success can affect relative fitness without changing the mean productivity of a population, these additional effects would lead to lower frequencies and lower fixation rates of deleterious alleles without higher costs to the mean fitness of the population.